Experimental Investigation on Heating Performance of Variable Refrigerant Flow System with Vapor Injection at Low Ambient Temperature - Song Peigang; Yu Pengfei; Dai Wenjie; Yan Huazhou (Zhileng xuebao)
Vapor injection technology is widely used in variable refrigerant flow (VRF) system to solve the problem of severe decrease of capacity in low-temperature environments. In this study, the key parameters such as pressure, temperature etc. and performance of a VRF system were tested and analyzed to get the control strategy of VRF system at low ambient temperature. The results show that the mass flow and state of the refrigerant flowing through the heat exchanger of outdoor unit are the main factors in the control of vapor injection for the performance of VRF system at low ambient environment. The better heating effect will be observed when the quality x of the refrigerant in the inject circuit is closer to 1. Therefore, the saturated vapor state of the refrigerant at the compressor supplementary port can be used as an important parameter for the thermal control of the VRF system at low ambient environment. However, the theoretical optimal pressure calculated by the suction and discharge pressure is not universal, cannot be used as an effective input parameter control for the low-temperature VRF system with vapor injection.